Stereotactic radiosurgery in the treatment of essential tremor – a systematic review - Bilski, Mateusz; Szklener, Katarzyna; Szklener, Sebastian; Rudzińska, Anna; Kluz, Natalia; Klas, Jakub; Rodzajewska, Anna; Kuryło, Weronika; Korga, Mateusz; Baranowska, Izabela; Mańdziuk, Sławomir (Frontiers in Neurology, 2024)
Essential tremor (ET) is the most common movement disorder in adults, with an estimated incidence of up to 1% of the population and 5% of people over 65 years of age. ET is manifested primarily by bilateral postural and kinetic tremor of the upper limbs with or without neurological symptoms and cognitive deficits. ET disrupts daily tasks and significantly lowers quality of life. Currently available medications alone are often insufficient to control severe symptoms. Several surgical treatment options are available, including stereotactic radiosurgery (SRS) -a minimally invasive treatment option aimed at relieving and controlling tremors. We conducted a systematic review of the scientific literature on the use of SRS in the treatment of ET using PubMed, Scopus, Web of Science, Cochrane, ScienceDirect and ClinicalTrials.gov registry and adhered to PRISMA guidelines. The results obtained confirm the high efficacy and safety of the SRS procedure, in treating drug-resistant intention tremor. Study results present high response rate reaching 80% and achievement of manual task improvement, lessening of the tremor and increase of the quality of life in majority of the operated patients. The method also stands out for its favorable balance of efficiency and cost. Ongoing research is crucial to refine patient selection criteria for this procedure and to further improve the technique's effectiveness.Essential tremor (ET) is the most common movement disorder in adults, with an estimated incidence of up to 1% of the population and 5% of people over 65 years of age [1]. The Movement Disorder Society (MDS) defines ET as isolated tremor syndrome of bilateral upper limb action